2017
DOI: 10.1371/journal.pone.0176610
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hyperoxia on brain activity: A resting-state and task-evoked electroencephalography (EEG) study

Abstract: A better understanding of the effect of oxygen on brain electrophysiological activity may provide a more mechanistic insight into clinical studies that use oxygen treatment in pathological conditions, as well as in studies that use oxygen to calibrate functional magnetic resonance imaging (fMRI) signals. This study applied electroencephalography (EEG) in healthy subjects and investigated how high a concentration of oxygen in inhaled air (i.e., normobaric hyperoxia) alters brain activity under resting-state and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In all these studies, however, behavioural state was not controlled and the influence of HYPEROXIA ON BRAIN ACTIVITY 5 physiological variables such as respiratory and heart rate changes were not taken into account. A recent study, however, reported decreases in EEG alpha activity during sustained-attention and task-evoked conditions, comparing 5-minute interleaved oxygen and control blocks (Sheng et al, 2017). While this study did control behavioural state under alert, sustained attention conditions, there has still been no systematic evaluation of the impact of hyperoxia on EEG oscillations in resting-state conditions.…”
Section: Introductionmentioning
confidence: 84%
“…In all these studies, however, behavioural state was not controlled and the influence of HYPEROXIA ON BRAIN ACTIVITY 5 physiological variables such as respiratory and heart rate changes were not taken into account. A recent study, however, reported decreases in EEG alpha activity during sustained-attention and task-evoked conditions, comparing 5-minute interleaved oxygen and control blocks (Sheng et al, 2017). While this study did control behavioural state under alert, sustained attention conditions, there has still been no systematic evaluation of the impact of hyperoxia on EEG oscillations in resting-state conditions.…”
Section: Introductionmentioning
confidence: 84%
“…Anesthesia was delivered for 6 min in air, then for 6 min in 80% oxygen, and finally in air again for 6 min. Anesthetic delivery was tested in air as well as in combination with 80% O 2 because anesthesia is often delivered in higher-than-air oxygen concentration and it has been shown that hyperoxia can affect neuronal activity in the awake state (Sheng et al 2017). Anesthesia was then stopped and recordings continued during the period of recovery for 20 minutes.…”
Section: Experimental Designmentioning
confidence: 99%
“…While different oscillatory states are associated with specific cognitive functions, our task did not specifically test a cognitive function, rather it simply demonstrated that there are oscillatory changes that occur under short‐term hyperoxia in resting‐state conditions. Sheng et al () recently demonstrated that hyperoxia was associated with reductions in alpha and beta power during both a sustained attention task and a visual ERP task. Our results similarly showed that hyperoxia was associated with decreases in alpha and beta power as well as proportion of detections during a resting‐state task when the eyes were opened but extended this to the comparison of eyes‐closed condition in which this decrease was lessened.…”
Section: Discussionmentioning
confidence: 99%
“…In all these studies, however, behavioral state was not controlled, and the influence of physiological variables such as respiratory and heart rate changes were not taken into account. A recent study, however, reported decreases in EEG alpha activity during sustained‐attention and task‐evoked conditions, comparing 5‐min interleaved oxygen and control blocks (Sheng, Liu, Mao, Ge, & Lu, ). While this study did control behavioral state under alert, sustained attention conditions, there has still been no systematic evaluation of the impact of hyperoxia on EEG oscillations in resting‐state conditions.…”
Section: Introductionmentioning
confidence: 96%